Presentation of the monograph by T.O.Kvyatkovskaya "Structure and function of the upper urinary tract" - journal "Morphologia", Editorial office (Морфологія / Morphologia / Morfologìâ, 2010)
The book is devoted to the study of morphological and physiological preconditions for the process of transporting urine through the upper urinary tract. The monograph presents the data of clinical anatomy, histological and ultrastructural structure of the renal pelvis and ureter in norm, with violation of urodynamics and after reconstructive operations using light, transmissive and scanning electron microscopy, histochemistry, X-ray diffraction analysis, X-ray and biomechanical methods.